A Case Report of Intra-articular Bee Venom Pharmacopuncture for Partial Tear of Triangular Fibrocartilage Complex - Lee, Kwangho; Ryu, YoungJin; Sun, Seungho; Kwon, Kirok (Korean Pharmacopuncture Institute, 2009)
Objective: This case was to report a case of Partial Tear of Triangular Fibrocartilage Complex treated by Intra-articular bee venom Pharmacopuncture. Methods: The patient was treated by Intra-articular bee venom Pharmacopuncture. The Effect of Treatment was evaluated by Visual Analog Scale(VAS) and Modified Mayo Wrist Score(Wrist Score). Results & Conclusions: After Treatment, Patient's VAS decreased and Wrist Score increased. For this results, Intra-articular Bee Venom Pharmacopuncture may be effective for Partial Tear of Triangular Fibrocartilage Complex.